2012
DOI: 10.7162/s1809-97772012000400010
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory muscle strength in asthmatic children

Abstract: Summary Introduction: Changes in the respiratory system of asthmatics are also due to the mechanical disadvantage caused by the increased airway resistance. Objective: The study aims to evaluate the respiratory muscle strength and nutritional status of asthmatic children. Method: This is a prospective descriptive and transversal study with 50 children aged 7 to 12 years, who were placed into 2 groups, asthmatic and non-asthmatic. Respiratory muscle strength was evaluated on the basis of maximal inspiratory pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
13
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 17 publications
6
13
1
1
Order By: Relevance
“…Our results are in agreement with reports by Marcelino et al (2012) andde Oliveira et al (2012), who found that inspiratory muscle strength in children with mild bronchial asthma is similar to inspiratory muscle strength in healthy controls. Compared to these studies (de Oliveira et al, 2012;Marcelino et al, 2012), we evaluated the PI max and PE max values in the percentage of predicted values, providing us with more accurate results. It is reported (Heinzmann-Filho et al, 2012;Neder, Andreoni, Lerario, & Nery, 1999;Wilson et al, 1984) that the PI max and PE max values depend on age, weight and height.…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…Our results are in agreement with reports by Marcelino et al (2012) andde Oliveira et al (2012), who found that inspiratory muscle strength in children with mild bronchial asthma is similar to inspiratory muscle strength in healthy controls. Compared to these studies (de Oliveira et al, 2012;Marcelino et al, 2012), we evaluated the PI max and PE max values in the percentage of predicted values, providing us with more accurate results. It is reported (Heinzmann-Filho et al, 2012;Neder, Andreoni, Lerario, & Nery, 1999;Wilson et al, 1984) that the PI max and PE max values depend on age, weight and height.…”
Section: Discussionsupporting
confidence: 94%
“…We confirmed a lower level of respiratory muscle strength in children with asthma than in healthy children, but a significant difference was reached only for the PE max in girls with asthma. Our results are in agreement with reports by Marcelino et al (2012) andde Oliveira et al (2012), who found that inspiratory muscle strength in children with mild bronchial asthma is similar to inspiratory muscle strength in healthy controls. Compared to these studies (de Oliveira et al, 2012;Marcelino et al, 2012), we evaluated the PI max and PE max values in the percentage of predicted values, providing us with more accurate results.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations